Re-purposing Chloroquine for Glioblastoma: Potential Merits and Confounding Variables - Weyerhäuser, Patrick; Kantelhardt, Sven R.; Kim, Ella L. (Frontiers in Oncology, 2018)
Chloroquine, one of the oldest antimalarials, has been implicated as a therapeutic sensitizer in different types of cancers. Reflecting a growing attention to the anti-neoplastic actions of this drug, over thirty trials have been initiated within the past five years to test the potential of chloroquine as an adjuvant treatment for different types of therapy-refractory cancers. Glioblastoma is one of the most aggressive human cancers shown to have a better response to standard therapy when combined with chloroquine. While there is considerable evidence for the efficacy and safety of chloroquine as an adjuvant treatment for cancer, the mechanisms underlying the tumor suppressive actions of this drug remain elusive. Up until recently, inhibitory effects of chloroquine on the late stage of autophagy was thought to be the major mechanism underlying cancer cells death from chloroquine. However, recent research provided compelling evidence that autophagy-inhibiting activities of chloroquine are dispensable for its ability to suppress tumor cells growth. These unexpected findings urge to explore the role of autophagy-independent activities of chloroquine and molecular mechanisms underlying the anti-cancer effects of this interesting drug. This review discusses the versatile actions of chloroquine in cancer cells with particular focus on glioma cells.